Lung Cancer Attributed Mortality Among 316,336 Early Stage Breast Cancer Cases Treated by Radiotherapy and/or Chemotherapy, 2000–2015: Evidence From the SEER Database - Abera, Semaw Ferede; Mikolajczyk, Rafael T.; Kantelhardt, Eva Johanna; Efremov, Ljupcho; Bedir, Ahmed; Ostheimer, Christian; Glowka, André; Vordermark, Dirk; Medenwald, Daniel (Frontiers in Oncology, 2021)
Objective: To estimate the risk of death from lung cancer in patients treated for breast cancer (BC) in relation to the general population. Methods: BC data, covering 2000 to 2015, were extracted from the Surveillance, Epidemiology and End Results-18 (SEER-18) cancer registry database. A comparison of lung cancer attributed mortality between BC patients and the general population was performed using standardized mortality ratios (SMRs) and SMRs conditional on survival length (cSMRs). Prognostic factors of lung cancer mortality were identified using flexible parametric modelling. Our model adjusts the effect of downstream (histopathological BC tumor grade and hormone receptor status) and upstream (age at diagnosis, ethnicity, and marital status) factors. Results: The median follow-up was 6.4 years (interquartile range, 3.0 - 10.3 years). BC cases who received only radiotherapy (cSMR= 0.93; 95%CI: 0.77 - 1.13), only chemotherapy (cSMR= 0.91; 0.62 - 1.33), and radio-and chemotherapy (cSMR= 1.04; 0.77 - 1.39) had no evidence of increased lung cancer mortality relative to the general population. The adjusted model identified that lung cancer mortality was higher for women who were older at diagnosis compared to those <50 years (ranging from HR50-59= 3.41 [95%CI: 2.72 - 4.28] to HR70-79 = 10.53 [95%CI: 8.44 - 13.13]) and for cases with negative estrogen and progesterone receptors (HR=1.38; 95% CI: 1.21 - 1.57). Compared to married cases, widowed, divorced, single or others had a 76%, 45%, and 25% higher hazard of lung cancer mortality, respectively. Lung cancer mortality was lower for American Indian/Alaska Native and Asian/Pacific Islander ethnicities (HR=0.51; 95% CI: 0.40 - 0.64) compared to BC cases with white ethnic background. Conclusions: There is no evidence for a higher lung cancer mortality in BC patients when compared to the general population.